THE INFLUENCE OF CASE METGODS ON THE LEARNING OUTCOME OF TUNISIAN HIGHER EDUCATION STUDENTS - ALOUI HIBA; QIANZHOU (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
There are more articles about the role of case studies in higher education class rooms. When discussing the role of case studies, it is usually related to the case discussion at the end of each chapter of business text books, rather than discussing what is not needed to discuss in a group of students working like a team, exploring everything they can. The conciseness or detail of the case depends on what you want students to be able to do in the course. The purpose of this article is to explore the types of cases that really require students to develop communication, problem solving, and critical thinking skills.